Corrosion of Silicon Nitride Materials in Aqueous Solutions. Issue 10 (8th August 2013) - Herrmann, M.; Green, D. J.
<x xml:space="preserve">Abstract</x> Silicon nitride ceramics are used under conditions where high strength, hardness, and wear resistance are necessary. The increasing use of Si3N4 ceramics in different environments demands an understanding of the relationships between microstructure and corrosion behavior. This study gives an overview of the behavior of silicon nitride in acids, bases, and hydrothermal conditions. It not only summarizes the literature data but also attempts to explain the mechanisms and to give some guidelines for the use of the materials in different environments. The stability of the ceramics against corrosion in acids and bases up to the boiling point is mostly controlled by the stability of the grain boundary. The stability can be predicted using the glass network theory. Materials with grain boundaries exhibiting a strong network, i.e., a high amount of SiO2 in the grain boundary, are stable in acids, but less stable under hydrothermal conditions and in basic solutions. Therefore, tailoring the grain boundaries can change the corrosion stability by several orders of magnitude. At temperatures above 200°C–250°C, the dissolution of the Si3N4 grains becomes a decisive factor determining the stability.